2020
DOI: 10.1002/apj.2448
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium ion removal using activated zeolite and chitosan

Abstract: Studies have previously been done on efficacies of chitosan and zeolite in ammonium ion (NH 4 + ) removal. However, no study compares the adsorption performance of natural zeolite (NZ) and activated NZ (ANZ) with high molecular weight chitosan (HMWC) and low molecular weight chitosan (LMWC).Hence, this study investigates the potentials of NZ, ANZ, LMWC, and HMWC in NH 4 + removal. The characteristics of NZ, ANZ, LMWC, and HMWC such as functional groups, surface morphology, elemental composition, zeta potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…The adsorption capacity of NaACC for ammonium was measured to increase from initial level of 0.07 mg/g to the maximal value of 0.77 mg/g during 144 h reaction (Figure 6c). The ammonium adsorption capacity of 0.77 mg/g achieved in this study was comparable with 0.769 mg/g reported for low molecular weight chitosan (LMW), but notably higher than 0.331 mg/g documented for high molecular weight chitosan (HMWC) 19 …”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The adsorption capacity of NaACC for ammonium was measured to increase from initial level of 0.07 mg/g to the maximal value of 0.77 mg/g during 144 h reaction (Figure 6c). The ammonium adsorption capacity of 0.77 mg/g achieved in this study was comparable with 0.769 mg/g reported for low molecular weight chitosan (LMW), but notably higher than 0.331 mg/g documented for high molecular weight chitosan (HMWC) 19 …”
Section: Resultssupporting
confidence: 80%
“…The ammonium adsorption capacity of 0.77 mg/g achieved in this study was comparable with 0.769 mg/g reported for low molecular weight chitosan (LMW), but notably higher than 0.331 mg/g documented for high molecular weight chitosan (HMWC). 19 In addition, data showed in Table 1 revealed that the treatment of groundwater with NaACC resulted in a notable increase of COD and BOD 5 from initial levels of 13.5 and 44.0 mg/L to 41.0 and 125.5 mg/L, respectively. This is attributed to the enhancement of total microbial colonies from 1050 to 9500 CFU/ml.…”
Section: Performance Of Naacc In Ammonium Removal From Natural Ground...mentioning
confidence: 96%
See 1 more Smart Citation
“…[43] A small band at 1438 cm À 1 is ascribed to the stretching vibration of CO 3 2À of calcite. [43] Although AgNP-zeolite showed similar peaks, slight alterations are observed in bands located on the 3700-3100 range cm À 1 and regions from 1020 to 600 cm À 1 affected by metal cations' interaction with the zeolite surface. A noticeable difference was the appearance of a peak at 1384 cm À 1 , which indicated the existence of Ag in the composite, and this result agreed with that reported by Zhang et al [44] The FT-IR spectra demonstrated the inflexibility of the silicate structure and the non-bond chemical interface between the silicate structure and AgNPs in the composite.…”
Section: Synthesis and Characterization Of Nanosilver Clay Compositesmentioning
confidence: 99%
“…The size of chitosan may vary such as 205 nm chitosan derived from crab shell [51], 331 nm from shrimp shell [52] and 1.1 nm synthesized from fish scales [53]. Chitosan and zeolite have been extensively being used to treat contaminants that commonly present in urban stormwater and runoff such as ammonia nitrogen [54,55], phosphate [56], dye and heavy metal [50,57].…”
Section: Zeolite and Chitosan As The Potential Nano-adsorbents In Gptsmentioning
confidence: 99%